'Fitting In' vs. 'Standing Out': How Social Enterprises Engage with Stakeholders to Legitimize their Hybrid Position. Issue 2 (3rd May 2020) - Granados, Maria L.; Rosli, Ainurul
Abstract: We investigate how social enterprises actively engage with their stakeholders to legitimize their hybrid position in addressing both social and businesses audience. This is particularly important in their effort to capturing stability (expectation to 'fit in') within an emerging field and at the same time to address change and growth (expectation to 'stand out') with their limited resources, in order to be profitable enterprises, while creating social value. We analyze in-depth interviews with senior members of 21 UK-based social enterprises and we find that for many SEs involved in legitimization exercise through the supportive system, collective system and stakeholders' impression. By outlining the integrated framework on stakeholder engagement for hybrid legitimacy, we found that (i) legitimization exercise through collective sharing of SE identity help to build SE image and legitimize SE socially driven mission, while (ii) legitimization through supportive system (resources and business advantage) help building credibility by demonstrating SE capability to grow economically.